Agroforestry for climate resilient agriculture and livelihood in arid regions of India - Roy, M.M.; Tewari, J.C. (Indian Journal of Agroforestry, 2020)
Arid regions of the world are diverse in terms of climate, soils, vegetation, animals and life styles and activities of people. One binding feature of all arid regions in the world is aridity. The hot arid regions of India cover an area of 31.70 million ha of which 61% is located in state of Rajasthan, thus, forms principal hot arid region of the country. Agroforestry is way of life in arid western Rajasthan and traditional agroforestry systems of the region appears to be evolved on the basis of rainfall gradient. In past three decades many improved agroforestry systems have been developed by CAZRI, Jodhpur. These systems are economically beneficial and environmentally sound. Agroforestry is both sequester carbon and produce a range of economic, environmental, and socioeconomic benefits. Research on agroforestry as an adaptation to climate change and as a buffer against climate variability is in the process of evolving. There are many pathways through which agroforestry qualify as an adaptation to climate change, especially in arid regions of the country. Moreover, agroforestry contributes to livelihood improvement in arid regions of India, where people have a long history of accumulated local knowledge. In fact, scattered trees on agricultural fields in arid regions of western Rajasthan are multipurpose in nature and they have ability to satisfy the expectations and aspiration of rural folk regarding production of their basic needs. Thus, agroforestry provides unique basis of life support in hot arid regions and has the ability to provide options for climate resilient agriculture.